Judicial constitutional comparativism at the UK Supreme Court - Lienen, Christina (2024)
In 2008, Lord Reed in his paper ‘Foreign precedents and judicial reasoning: the American debate and British practice’ noted the lack of full scholarly consideration of judicial comparativism in the UK. Ten years later, judicial reference to foreign judgments is still a very common phenomenon in this jurisdiction, however very little has been written about it. This paper assesses the UK Supreme Court’s constitutional law jurisprudence in light of the main themes and arguments underlying the international debate con cerning judicial comparativism. I argue that: (i) the use of foreign law is constitutionally legitimate where clear statutory language is respected; (ii) transferability concerns are mitigated by the interwoven ness of the global common law system; and (iii) methodology concerns are mitigated by the UK Supreme Court’s flexible, humble approach, which applies careful scrutiny to the foreign authorities put before it. Foreign judgments, I conclude, are never followed blindly or arbitrarily, and perhaps this is why there is no domestic debate about judicial comparativism, not even in the constitutional sphere.